Análisis Financiero del nivel de endeudamiento en la empresa Agrofilter Ltda Duitama durante el 2018 -2019 (2021)
Financial analysis is an important tool that generates value for organizations, it also serves as the basis for diagnosing, comparing, correcting and exalting the true situation of the company, this writing focuses on analyzing the level of indebtedness of the company Agrofilter Ltda located in the city of Duitama, through its financial structure of great economic importance within the organization's management, evaluating the liability and equity accounts, in order to provide solid information for decision-making and guarantee the entity the support and positioning over time.